Beneficial Effects of Silibinin Against Kainic Acidinduced Neurotoxicity in the Hippocampus in vivo - Kim, Sehwan; Jung, Un Ju; Oh, Yong-Seok; Jeon, Min-Tae; Kim, Hyung-Jun; Shin, Won-Ho; Hong, Jungwan; Kim, Sang Ryong (Experimental neurobiology, 2017)
Silibinin, an active constituent of silymarin extracted from milk thistle, has been previously reported to confer protection to the adult brain against neurodegeneration. However, its effects against epileptic seizures have not been examined yet. In order to investigate the effects of silibinin against epileptic seizures, we used a relevant mouse model in which seizures are manifested as status epilepticus, induced by kainic acid (KA) treatment. Silibinin was injected intraperitoneally, starting 1 day before an intrahippocampal KA injection and continued daily until analysis of each experiment. Our results indicated that silibinin-treatment could reduce seizure susceptibility and frequency of spontaneous recurrent seizures (SRS) induced by KA administration, and attenuate granule cell dispersion (GCD), a morphological alteration characteristic of the dentate gyrus (DG) in temporal lobe epilepsy (TLE). Moreover, its treatment significantly reduced the aberrant levels of apoptotic, autophagic and pro-inflammatory molecules induced by KA administration, resulting in neuroprotection in the hippocampus. Thus, these results suggest that silibinin may be a beneficial natural compound for preventing epileptic events. KCI Citation Count: 5